Respuesta :

[tex]3(x - 4) - 14 = 2(x - 7) + 6 \\ \\ 3x - 12 - 14 = 2x - 14 + 6 \ / \ expand \\ \\ 3x - 26 = 2x - 14 + 6 \ / \ simplify \\ \\ 3x - 26 = 2x - 8 \ / \ simplify \\ \\ 3x = 2x - 8 + 26 \ / \ add \ 26 \ to \ each \ side \\ \\ 3x = 2x + 18 \ / \ simplify \\ \\ 3x - 2x = 18 \ / \ subtract \ 2x \ from \ each \ side \\ \\ x = 18 \ / \ simplify \\ \\ [/tex]

The final result is x = 18.
3(x - 4) - 14 = 2(x - 7) + 6
⇒ 3x+ 3(-4) -14= 2x+ 2*7+ 6 (distributive property)
⇒ 3x -12 -14= 2x -14+ 6
⇒ 3x+ (-12 -14)= 2x+ (-14+ 6) (combine like terms)
⇒ 3x -26= 2x -8
⇒ 3x -2x= -8+ 26 (inverse operation)
⇒ x= 18

Final answer: x= 18.